2021
DOI: 10.1371/journal.pone.0261453
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bio-logging on body weight change of the Eurasian beaver

Abstract: Bio-logging is a common method to collect ecological data on wild animals, but might also induce stress, reduce body condition, and alter behavior. Eurasian beavers (Castor fiber) are a semi-aquatic and nocturnal species that are challenging to observe in the wild. Bio-loggers are hence useful tools to study their behaviour and movements, but this raises concerns of potential negative impacts of tagging. To investigate the potential negative impacts of glue-on tags, we compared body weight change for tagged an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Physiological impacts to walkers are often attributed to disruption of fur or feathers, leading to compromised thermoregulation and therefore elevated energy expenditure [51] or reduced body condition [52].…”
Section: A Impacts To Walkersmentioning
confidence: 99%
“…Physiological impacts to walkers are often attributed to disruption of fur or feathers, leading to compromised thermoregulation and therefore elevated energy expenditure [51] or reduced body condition [52].…”
Section: A Impacts To Walkersmentioning
confidence: 99%
“…Mark–recapture studies using individual beaver recognition have relied so far on PIT tags (Briggs et al., 2021 ; Mayer et al., 2022 ), GPS tags (Mayer et al., 2019 ), ear tags, modified VHF‐ear tags for the tail, as well as neck radio collars or backpack harnesses (Arjo et al., 2008 ) or even intraperitoneal radio transmitters (Ranheim et al., 2004 ). However, it has been shown that these mark–recapture actions can result in negative effects, such as loss of body mass or even death (Mortensen & Rosell, 2020 ; Ranheim et al., 2004 ; Robstad et al., 2021 ). Some animals exhibit natural tail wounds and scars, which can be used for individual identification, however not every animal shows such marks, and in particular young beavers do not generally exhibit wounds or scars (Mayer et al., 2019 , 2020 ; Schwaiger & Schwemmer, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have utilized either external (Gracanin et al 2018;Littlewood et al 2021;Mos and Hofmeester 2020) or internal lenses (McCleery et al 2014;Uhe et al 2020) to adjust the focal distance between the camera and the subject matter. By doing so, features are recorded in focus, at a greater resolution, allowing researchers to perform confident identification of individuals within a species based on either natural markings (Bradfield 2004;Karanth 1995;Kelly 2001;Hiby et al 2009), physical tags or notches (Briggs et al 2021;Jung et al 2020;Ranheim et al 2004;Robstad et al 2021) or natural scars (Ardovini et al 2007;Hillman et al 2003). The application of such a camera trapping methodology has great potential for a number of small to medium sized species (De Bondi et al 2010;Gracanin et al 2018;Uhe et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, even if trained personnel carry out these techniques, studies have revealed that these methods can have a negative impact on the animals. Especially the body mass of beavers decreases with the number of captures during the tagging period (Mortensen and Rosell 2020;Robstad et al 2021). In addition, the use of anaesthetics always carries the risk that animals may die during the procedure (Ranheim et al 2004).…”
Section: Introductionmentioning
confidence: 99%